Form, Meaning, and Functions of the Nundang Padi Tradition: A Qualitative Study in Selali Village, South Bengkulu, Indonesia - Herpina Rahmadayanti; Irwan Satria; Dina putri Juni Astuti (Yayasan Darussalam Bengkulu, 2023)
This study investigates the cultural significance of the Nundang Padi tradition practiced in Selali Village, Pino Raya District, South Bengkulu, Indonesia. The research aimed to explore both the meaning and the social functions of this agrarian ritual, which has been maintained across generations as a form of oral tradition. Employing a qualitative descriptive design, data were collected through observation, in-depth interviews with cultural leaders and community members, and documentation of ritual practices. The findings reveal that the Nundang Padi tradition embodies two layers of meaning: denotative, reflecting gratitude for the harvest and preparation of seeds for the next planting cycle, and connotative, representing emotional and symbolic attachments to ancestral heritage and harmony with nature. In terms of function, the ritual serves recreational and aesthetic purposes through performances and dances, conveys moral and didactic values by transmitting cultural norms to younger generations, and fulfills religious functions by expressing collective prayers for safety and prosperity. These findings highlight the importance of Nundang Padi as an intangible cultural heritage that sustains social cohesion and reinforces community identity in an era of modernization. The study contributes to broader discussions on cultural resilience and underscores the need to preserve oral traditions as vital elements of sustainable cultural development.